Agent and multi-agent systems : technologies and applications : 9th KES International Conference, KES-AMSTA 2015, Sorrento, Italy, June 2015, Proceedings /: technologies and applications : 9th KES International Conference, KES-AMSTA 2015, Sorrento, Italy, June 2015, Proceedings. ([2015]) - Unknown
No abstract available